2018
DOI: 10.1007/s00204-018-2239-3
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal arsenic exposure is associated with increased plasma IGFBP3 concentrations in 9-year-old children partly via changes in DNA methylation

Abstract: Exposure to inorganic arsenic (As), a carcinogen and epigenetic toxicant, has been associated with lower circulating levels of insulin-like growth factor 1 (IGF1) and impaired growth in children of pre-school age. The aim of this study was to assess the potential impact of exposure to As on IGF1 and insulin-like growth factor-binding protein 3 (IGFBP3) as well as DNA methylation changes in 9-year-old children. To this end, we studied 9-year-old children from a longitudinal mother–child cohort in rural Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In addition, cg15019001 (HLA-DPB2), cg22809683 (LAMC1), cg07466788 (SLC16A3), cg19504605 (ZFP41), cg22143856 (ZNF389), cg13251666, and cg13844779, identified as differentially methylated between As-exposed and control families in China (n = 102) (Guo et al 2018), were nominally significant in our analyses. Among 4,427 CpGs previously associated with in utero As exposure (Cardenas et al 2015;Gliga et al 2018;Green et al 2016;Kaushal et al 2017;Kile et al 2014;Rojas et al 2015) 179 were nominally significant in the current study. Demanelis et al also reported all nominally significant loci, allowing us to check for significance of our FDR-significant CpGs.…”
Section: Evaluation Of Previously Identified Differentially Methylatesupporting
confidence: 51%
See 2 more Smart Citations
“…In addition, cg15019001 (HLA-DPB2), cg22809683 (LAMC1), cg07466788 (SLC16A3), cg19504605 (ZFP41), cg22143856 (ZNF389), cg13251666, and cg13844779, identified as differentially methylated between As-exposed and control families in China (n = 102) (Guo et al 2018), were nominally significant in our analyses. Among 4,427 CpGs previously associated with in utero As exposure (Cardenas et al 2015;Gliga et al 2018;Green et al 2016;Kaushal et al 2017;Kile et al 2014;Rojas et al 2015) 179 were nominally significant in the current study. Demanelis et al also reported all nominally significant loci, allowing us to check for significance of our FDR-significant CpGs.…”
Section: Evaluation Of Previously Identified Differentially Methylatesupporting
confidence: 51%
“…Among 4,427 CpGs previously associated with in utero As exposure ( Cardenas et al. 2015 ; Gliga et al. 2018 ; Green et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also adjusted all the models for urinary arsenic (sum of metabolites; log2-tranformed) at each exposure time point because arsenic has previously been adversely associated with IGF-1 and IGFBP3 in this cohort (Ahmed et al. 2013; Gliga et al. 2018) and because it may occur in the same dietary sources as cadmium, particularly in rice (Kippler et al.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is hard to postulate if the LYRM2 methylation change is epigenetic toxicity, adaptation or just a neutral biomarker of arsenic. This is the case with another arsenic-related study [109], and with a large body of research on the effect of the environment on epigenetic variation.…”
Section: Challenges and Outlookmentioning
confidence: 90%